2010
DOI: 10.1016/j.jemermed.2007.09.045
|View full text |Cite
|
Sign up to set email alerts
|

Interpreter Services in Emergency Medicine

Abstract: Emergency Department (ED) physicians are routinely confronted with problems associated with language barriers. It is important for emergency health care providers and the health system to strive for cultural competency when communicating with members of an increasingly diverse society. Solutions include professional interpretation, telephone interpretation, the use of bilingual staff members, the use of ad hoc interpreters, and more recently the use of mobile computer technology at the bedside. Each method car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 26 publications
(20 reference statements)
0
27
0
1
Order By: Relevance
“…OPI offers an interesting mix of benefits and challenges. Its impersonal quality enables confidential communication about sensitive or emotionally disturbing information [ 25 , 20 ], but the loss of nonverbal input can also be a barrier to an optimal exchange [ 2 , 26 , 27 , 6 , 25 , 28 ]. Providers also cite inconvenience and the extra time it requires as disadvantages of OPI [ 23 , 26 ], and suggest its utility may be limited to certain types of provider-patient interactions, such as direct information exchange [ 29 , 20 ].…”
Section: Telephone Interpretation Services (Opi)mentioning
confidence: 99%
See 1 more Smart Citation
“…OPI offers an interesting mix of benefits and challenges. Its impersonal quality enables confidential communication about sensitive or emotionally disturbing information [ 25 , 20 ], but the loss of nonverbal input can also be a barrier to an optimal exchange [ 2 , 26 , 27 , 6 , 25 , 28 ]. Providers also cite inconvenience and the extra time it requires as disadvantages of OPI [ 23 , 26 ], and suggest its utility may be limited to certain types of provider-patient interactions, such as direct information exchange [ 29 , 20 ].…”
Section: Telephone Interpretation Services (Opi)mentioning
confidence: 99%
“…One review found just 18 % of hospitals in the United Kingdom used a formal interpreter agency [ 15 ]; and a review of pediatricians found low use in all states in the United States, regardless of demographics – a pattern which has improved only modestly since 2004 [ 16 , 17 ]. The most commonly cited reasons for low uptake of these services include cost issues - such as lack of reimbursement mechanisms - and timeliness of access [ 18 , 2 , 19 , 20 , 6 , 21 , 17 , 22 ]. Other noted barriers include presence of bilingual staff [ 23 ] and providers’ belief that patients prefer using their relatives over professional interpreters [ 24 , 14 ], though some studies with patients have disputed the latter [ 5 , 12 ].…”
mentioning
confidence: 99%
“…11, 13 Finally, LEP patients tend to rely more heavily on emergency departments, and are less likely to use preventive and primary care services compared to language concordant or English speaking-patients. 2, 10, 14 …”
Section: Introductionmentioning
confidence: 99%
“…29 Thus, there is a paucity of data on which to base decisions about funding and implementation of language assistance services. 14 Video conferencing medical interpretation is a new modality that uses video conferencing technology ( via mobile, closed-circuit televisions) to interpret in real time from a remote location while maintaining three-way non-verbal communication among the patient, interpreter, and clinician. Through centralization of shared language services, video conferencing interpretation offers great potential for increasing language access and reducing costs across health care sites and systems.…”
Section: Introductionmentioning
confidence: 99%
“… 26 The availability of family members to interpret in the context of a hectic and chaotic setting where time pressures are high and the engagement of ad hoc interpreters is the norm appears to be an even greater obstacle to professional interpreter engagement in the ED. 24 , 26 Older Greek, Italian, or Spanish patients may be more likely to be accompanied by adult children to the ED who may be more willing to interpret. Our finding that older people speaking European languages such as Italian, Greek, and Spanish are significantly less likely to be provided with a professional interpreter through their hospital journey is consistent with availability and willingness of family members to interpret, which can influence clinician decision making more than cost.…”
Section: Discussionmentioning
confidence: 99%